Analysis of the general index of modelling in interior lighting - Pracki, Piotr; Komorzycka, Paulina (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Directionality of light and modelling effects impact lighting quality in interiors. Modelling effects depend on the photometric characteristics of luminaires and their layout but also interior size and reflectance. This research aims to evaluate lighting design limitations and the characteristics of the impact of interior and luminaires on modelling effects, as well as elaborate a prediction method of modelling effects in interior lighting. The general index of modelling was used for the analysis of modelling effects in interiors. The implementation of the research objectives was based on simulation and statistical analysis. 432 situations, varied interior size, and reflectance, the lighting class, luminaire downward luminous intensity distribution, and layout were considered. The results show that achieving the required range of the general index of modelling in interior lighting is substantially limited. The general index of modelling is impacted the most by the layout of luminaires. The elaborated multiple linear regression models can have a practical use for interior lighting design and analysis in terms of obtaining the required range of the general index of modelling.